2016
DOI: 10.35489/bsg-rise-wp_2016/009
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Effective Teaching in Developing Countries

Abstract: There is growing interest in observing teachers' classroom practice, for formative feedback to teachers, teacher performance evaluation and incentives, program impact evaluation, and research on the determinants of student learning. For observations to generate meaningful data, they must be carried out using valid instruments, standardized protocols, and trained observers. A number of different observation instruments have been used in the US, but only two have gained any traction to date in developing countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Bruns et al (2016), comparing CLASS with another widely-used observation instrument (Stallings) find that when using them within the same developing country context (Chile), both instruments produce consistent assessments of teachers’ effectiveness in managing their classrooms and ensuring student learning.…”
Section: Measuring Teacher Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruns et al (2016), comparing CLASS with another widely-used observation instrument (Stallings) find that when using them within the same developing country context (Chile), both instruments produce consistent assessments of teachers’ effectiveness in managing their classrooms and ensuring student learning.…”
Section: Measuring Teacher Effectivenessmentioning
confidence: 99%
“…In summary, an increasing body of global evidence on teacher effectiveness has found that teachers are differentially effective in producing student achievement; what they do and how they do it is of crucial importance for student outcomes. However, this cannot be predicted by teachers’ formal qualifications or other aspects of observable teacher characteristics (Bruns et al, 2016). By contrast, the contractual arrangements for teachers and measures of teacher effort do predict student achievement in some contexts.…”
Section: Measuring Teacher Effectivenessmentioning
confidence: 99%
“…The literature on classroom interactions focuses on the nature, quality, and quantity of interactions between teachers and students in different domains in the classroom (Pianta et al 2008a;Stallings and Knight 2003;Bruns et al 2016). CLASS does not examine the content of what is being taught or the specific activities carried out.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…A different strand of the literature examines what happens in the classroom. It generates quantitative data on teachers' practice by coding segments of time and observing activities and participation (Bruns et al 2016). The coding strategy and the variables generated for this study are more closely related to this line of research.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…The project found that the best composite measure is based primarily on student test scores (value‐added), with a small weight for lesson observation and student feedback (Kane, McCaffrey, Miller, & Staiger, 2013). Lesson observations might, however, also help to understand why some teachers are more effective than others, by identifying specific practices that are associated with improved outcomes (see, for example, Araujo, Carneiro, Cruz‐Aguayo, & Schady, 2016; Bruns, Gregorio, & Taut, 2016; Carnoy, Ngware, & Oketch, 2015; Ngware, Ciera, Musyoka, & Oketch, 2015).…”
Section: Introductionmentioning
confidence: 99%